2021
DOI: 10.7717/peerj.12118
|View full text |Cite
|
Sign up to set email alerts
|

The LEAF questionnaire is a good screening tool for the identification of the Female Athlete Triad/Relative Energy Deficiency in Sport among young football players

Abstract: Background It has been noticed that Female Athlete Triad (Fat) and Relative Energy Deficiency (Red-S) in Sport are characterized by the symptoms of impaired endocrine-metabolic function and bone health in female athletes. In addition, it may be evaluated with a qualitative tool, such as Low Energy Availability in Females questionnaire (LEAF-Q) and quantitative measurements: bone mineral density (BMD), resting energy expenditure (REE), body composition, 24-hour dietary recall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, they were unable to adequately meet their iron needs during the season ( 29 ). Calcium intake for both control and intervention groups (1009.3 mg ± 392.1 mg, 1,096 mg ± 431.7) was lower than RDA for adolescent female athletes (1,300 mg) ( 34 ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, they were unable to adequately meet their iron needs during the season ( 29 ). Calcium intake for both control and intervention groups (1009.3 mg ± 392.1 mg, 1,096 mg ± 431.7) was lower than RDA for adolescent female athletes (1,300 mg) ( 34 ).…”
Section: Resultsmentioning
confidence: 84%
“…Cross-sectional studies indicate that the estimation of low EA in athletes varies from 51 to 63% ( 25 , 33 ). In a study conducted by Łuszczki et al ( 34 ) it was found that 64.7% of participants were classified as being at risk for low energy availability according to their LEAF-Q scores among young football players. The researchers noted that the mean age of the study group was lower (15,41 years) than most in the literature ( 35 ) which could be a probable explanation for the lower level of sports nutrition knowledge among this athlete group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the percentage of training days lost due to injuries lasting 15 to 21 days was 11%, with a similar percentage for those injuries more than 22 days. However, a higher percentage of lost training days was reported by Łuszczki et al [ 40 ], who also studied football players. The number of lost training days due to injury of 15 to 21 days was 14.7%, and above 22 days, it reached 20.6%.…”
Section: Discussionmentioning
confidence: 83%
“…Efforts have been made to extend research on RED-S and associated risk factors to other populations beyond female aesthetic and endurance athletes (e.g., recreational exercisers, male cyclists, synchronised swimming; and male combat athletes [ 17 20 ]), however little is available on team sport athletes. Current research using team sport athletes has explored risk factors and symptoms associated with RED-S or female athlete triad such as menstrual function, bone health and energy availability in female footballers [ 21 25 ] and volleyball players [ 26 ]. Numerous sports have received little attention despite potentially having an athlete groups at risk of the female athlete triad, and by extension RED-S. One such example is netball, a team sport that is characterised as a high-intensity intermittent sport, and that is growing in both popularity and professionalism.…”
Section: Introductionmentioning
confidence: 99%